Antifouling membrane surface construction: Chemistry plays a critical role - Zhao, Xueting; Zhang, Runnan; Liu, Yanan; He, Mingrui; Su, Yanlei; Gao, Congjie; Jiang, Zhongyi (Journal of membrane science, 2018)
Membrane technology has been broadly utilized in water purification including wastewater treatment, seawater or brackish water desalination. However, it often suffers from the severe membrane fouling due to the nonspecific interactions between membrane surface and foulants. Antifouling membrane surface construction thus becomes an everlasting and ubiquitous issue, where chemistry plays a critical role in membrane material design, hierarchical structure manipulation, antifouling mechanism integration and separation performance intensification. Many emerging chemistries enable the rational design and construction of state-of-the-art antifouling membrane surfaces. This review will highlight the recent progress in antifouling membrane surface construction with a focus on five promising classes of chemistries: bioinspired adhesion chemistry, supramolecular chemistry, mineralization chemistry, click chemistry and coupling chemistry. The contribution of chemistries to the physico-chemical structure, antifouling properties, separation performance and long-term durability of membranes will be elaborated. Major challenges and perspectives on future directions of chemistries in antifouling membrane surface construction will also be tentatively delineated. Antifouling membranes hold great promise in the sustainable development of membrane technology for water purification. Chemistry plays a critical role in antifouling membrane surface construction due to their broad diversity and high efficiency. The recent advances in some representative chemistries for material design, structure manipulation, mechanism integration and property intensification of antifouling membranes are highlighted. [Display omitted] •Critical role of chemistry in antifouling membrane surface construction is surveyed.•Bioadhesion, supramolecular, mineralization, click and coupling chemistry are covered.•Contribution of chemistry to membrane application performance is highlighted.•Perspective of chemistry on antifouling membrane surface construction is proposed.